Avaliação da potencialidade do uso de hidrogéis poliméricos na terapeutica de leishmaniose cutânea - Silva, Vanessa Bezerra da (2015)
Poly(vinyl alcohol) - PVA is a high hydrophilic semicrystalline polymer which has excellent properties such as good chemical resistance and high biodegradability and biocompatibility. Due to its semi-crystalline nature, crystalline domains, under controlled conditions, may act as physical crosslinking points, while maintaining the integrity of the structure under swelling. This feature makes PVA hydrogels promising for the development of drug, or other bioactive substances, delivery systems. Another interesting feature of this kind of hydrogels is the ability to form high stable network from crystalline domains formed through freezing and thawing cycles. This method shows the formation of crystallites which act as physical crosslinks while maintaining the insolubility of the material in water. Recently many studies show the use of nanostructures to improve mechanics properties and diffusional behavior of small molecules. Paromomycin is an aminoglycoside antibiotic widely used for cutaneous leishmaniasis therapeutics in Brazil. In the last years some studies have revealed that the patience adhesion to the treatments of cutaneous leishmaniasis with ointments form is low. Therefore hydrogels are an interesting alternative to the ointment forms. As the main objective of this work was the preparation and characterization of poly(vinyl alcohol) hydrogels containing sepiolite nanoparticles for the preliminary feasibility of using as controlled release system for paromomycin, hydrogels were prepared by cryogelation process. This ensures the formation of the hydrogel, as long as the crystalline domains formed during the PVA cycles act as crosslinking points, allowing the membranes water transport measurements of the drug in the presence of sepiolite. In this investigation membranes were characterized by differential calorimetry, thermogravimetry and X-ray diffraction. Furthermore polymer retention, swelling in simulated body fluid, hemocompatibility and drug delivery were studied to establish structure-properties correlations. The results show that cryogelation cycles significantly alter the swelling of the membranes; interactions polymer-nanoparticle increases the rigidity of the amorphous phase. Comparing to pure PVA hydrogels, in nanocomposites hydrogels the hemolysis decreased. Increasing the percentage of nanoparticles the membrane crystallinity decreases. The samples degradation profile, the thermal stability and drug delivery profile are not modified by the amount of nanoparticles incorporated.